Role of the miR-17∼92 cluster family in cerebellar and medulloblastoma development - Zindy, Frederique (The Company of Biologists, 2014)
The miR-17∼92 cluster family is composed of three members encoding microRNAs that share seed sequences. To assess their role in cerebellar and medulloblastoma (MB) development, we deleted the miR-17∼92 cluster family in Nestin-positive neural progenitors and in mice heterozygous for the Sonic Hedgehog (SHH) receptor Patched 1 (Ptch1(+/−)). We show that mice in which we conditionally deleted the miR-17∼92 cluster (miR-17∼92(floxed/floxed); Nestin-Cre(+)) alone or together with the complete loss of the miR-106b∼25 cluster (miR-106b∼25(−/−)) were born alive but with small brains and reduced cerebellar foliation. Remarkably, deletion of the miR-17∼92 cluster abolished the development of SHH-MB in Ptch1(+/−) mice. Using an orthotopic transplant approach, we showed that granule neuron precursors (GNPs) purified from the cerebella of postnatal day 7 (P7) Ptch1(+/−); miR-106b∼25(−/−) mice and overexpressing Mycn induced MBs in the cortices of naïve recipient mice. In contrast, GNPs purified from the cerebella of P7 Ptch1(+/−); miR-17∼92(floxed/floxed); Nestin-Cre(+) animals and overexpressing Mycn failed to induce tumors in recipient animals. Taken together, our findings demonstrate that the miR-17∼92 cluster is dispensable for cerebellar development, but required for SHH-MB development.